Sustainable fashion in the context of hypermodernity - Maicon Douglas Livramento Nishimura (Projetica, 2019)
Considering the adaptability of fashion to the changes in society and the reconfiguration of the production system, that is in search of more sustainable practices, the objective of this paper is to develop a fashion collection based on the principles of sustainable fashion in the context of the hypermodernity. Thus, we observed that the current reflections on the topic are aligned with the emergence of the socio-environmental agenda, but – under the perspective of Slow Fashion – several difficulties arise, mainly in relation to the use of raw materials.